2000
DOI: 10.1111/j.1749-6632.2000.tb06298.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in the Matrix Metalloproteinase Family: Effects on Function and Disease Progressiona

Abstract: Atherosclerosis is an example of a complex trait, where the course of the disease is influenced by a combination of common variation in a constellation of genes and the effect of a wide range of environmental variables. Thus, the underlying disease mechanisms will be modulated by genetic diversity and the effect this diversity has on an individual's response to environmental challenges such as smoking, diet, and exercise. Unlike the consequences of mutations in severe single‐gene disorders on protein function,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The discovery of polymorphisms in MMP promoters that alter gene expression has revealed strong associations between these genetic variants and increased susceptibility to the development of malignancies and other diseases (Henney et al, 2000;Ye, 2000). The most extensively studied MMP SNP in relation to cancer is the À1607 bp insertion/deletion in the MMP-1 promoter (Rutter et al, 1998;Nishioka et al, 2000;Ghilardi et al, 2001;Zhu et al, 2001;Hinoda et al, 2002;Tower et al, 2002;Wyatt et al, 2002;Zinzindohoue et al, 2005;Elander et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of polymorphisms in MMP promoters that alter gene expression has revealed strong associations between these genetic variants and increased susceptibility to the development of malignancies and other diseases (Henney et al, 2000;Ye, 2000). The most extensively studied MMP SNP in relation to cancer is the À1607 bp insertion/deletion in the MMP-1 promoter (Rutter et al, 1998;Nishioka et al, 2000;Ghilardi et al, 2001;Zhu et al, 2001;Hinoda et al, 2002;Tower et al, 2002;Wyatt et al, 2002;Zinzindohoue et al, 2005;Elander et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Changed expression of MMPs has been implicated in the pathogenesis of several cardiovascular disorders, including atherosclerosis (Newby, 2005). Recent observations suggest that genetic variation affects the expression of MMPs, which may contribute to the occurrence of cardiovascular disease (Henney et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been observed that T allele carriers in comparison with CC homozygotes were overrepresented in a subgroup of patients with triple-vessel disease [20]. Recent research suggested that –1562C/T affected the expression of MMP9, which may contribute to the occurrence of cardiovascular disease [21]. A common R279Q polymorphism of the MMP9 exon 6 leading to an amino acid substitution in the enzymatic active site has also been described [7,22,23].…”
Section: Introductionmentioning
confidence: 99%